PENGARUH TIGA JENIS PUPUK KANDANG TERHADAP pH, C-ORGANIK, N-TOTAL TANAH DAN HASIL TANAMAN BUNCIS (Phaseolus vulgaris L.) PADA TANAH ULTISOL - LAMPOSO, RAMADAN; DARWIS, DARWIS; RESMAN, RESMAN; GINTING, SAHTA; ALAM, SYAMSU; NAMRIAH, NAMRIAH (Jurnal Agroteknos, 2023)
Ultisol still has the potential for the development of dry land agriculture. However, the utilization of Ultisol faces soil fertility constraints which can inhibit plant growth, especially bean plants, if not managed properly. The aim of the study was to determine the effect of manure and dosage on pH, organic C, total N, and yield of chickpea plants (Phaseolus vulgaris L.). The research was conducted at Field Laboratory II, Faculty of Agriculture, Halu Oleo University, from November 2021 to January 2022. The research was arranged according to a Split Plot Design with a factorial pattern. The main plot consists of three levels, namely chicken manure (KA), goat manure (KK) and cow manure (KS). Subplots consisted of 4 levels, namely: without manure (D0), 2% manure (D1), 4% manure (D2) and 6% manure (D3). The results showed that chicken manure, goat manure and cow manure had an effect on soil pH, C-organic and N-total. The highest increase in soil pH was achieved in chicken manure treatment (6.3), followed by goat manure and the lowest in cow manure. The highest increase in C-organic occurred in the chicken manure treatment (2.07%), then goat manure and the lowest was cow manure. The highest increase in N-total occurred in the cow manure treatment (0.13%), then the chicken manure and the lowest was in the goat manure treatment. There was no significant interaction between manure and dosage on bean yields. Manure has an independent effect on the number of pods and pod weight. The highest number of pods and the heaviest weight were achieved in the KK treatment with 20.17 pods and 97.17 g weight, followed by the KA treatment with 17.00 pods and 75.75 g weight and in the KS treatment with 3.25 pods and weighs 12.17 g.